Stage-specific roles of FGF2 signaling in human neural development - Grabiec, Marta; Hříbková, Hana; Vařecha, Miroslav; Střítecká, Dana; Hampl, Aleš; Dvořák, Petr; Sun, Yuh-Man (Stem cell research, 2016)
This study elucidated the stage-specific roles of FGF2 signaling during neural development using in-vitro human embryonic stem cell-based developmental modeling. We found that the dysregulation of FGF2 signaling prior to the onset of neural induction resulted in the malformation of neural rosettes (a neural tube-like structure), despite cells having undergone neural induction. The aberrant neural rosette formation may be attributed to the misplacement of ZO-1, which is a polarized tight junction protein and shown co-localized with FGF2/FGFR1 in the apical region of neural rosettes, subsequently led to abnormal neurogenesis. Moreover, the FGF2 signaling inhibition at the stage of neural rosettes caused a reduction in cell proliferation, an increase in numbers of cells with cell-cycle exit, and premature neurogenesis. These effects may be mediated by NUMB, to which expression was observed enriched in the apical region of neural rosettes after FGF2 signaling inhibition coinciding with the disappearance of PAX6+/Ki67+ neural stem cells and the emergence of MAP2+ neurons. Moreover, our results suggested that the hESC-based developmental system reserved a similar neural stem cell niche in vivo.
Keywords: fibroblastový růstový faktor 2; Microtubule-Associated Proteins; RNA interference; Cell Line; Time-Lapse Imaging; Morpholines; chromony; Neural developmental modeling; lidské embryonální kmenové buňky; Neural stem cell niche; Receptor, Fibroblast Growth Factor, Type 1; membránové proteiny; časosběrné zobrazování; signální transdukce; buněčná diferenciace; proteiny nervové tkáně; Membrane Proteins; Pyrimidines; proteiny asociované s mikrotubuly; imunohistochemie; neurony; Chromones; Signal Transduction; receptor fibroblastových růstových faktorů, typ 1; RNA, Small Interfering; Embryonic stem cells; Zonula Occludens-1 Protein; Neural fate; lidé; Neurogenesis; Neural Stem Cells; Immunohistochemistry; Humans; malá interferující RNA; pyrimidiny; Neurons; morfoliny; buněčné linie; Human Embryonic Stem Cells; FGF2 signaling; neurogeneze; nervové kmenové buňky; Fibroblast Growth Factor 2; RNA Interference; protein zonula occludens 1; Nerve Tissue Proteins; Cell Differentiation